2013
DOI: 10.1177/0194599813481430
|View full text |Cite
|
Sign up to set email alerts
|

Preformed vs Intraoperative Bending of Titanium Mesh for Orbital Reconstruction

Abstract: All 3 techniques provide equivalent orbital volume correction. However, preformed mesh implants have many advantages based on contour accuracy, ease of use, and relative cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 10 publications
2
53
0
5
Order By: Relevance
“…5,6 A recent study by Strong et al reported that this had "the greatest contour accuracy" when compared with freehand bending in cadaveric orbits. 7 However, they also noted that stereolithographic modeling incurred the highest cost. 7 Currently, the price of anatomical models outsourced to medical modeling companies can be considerable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 A recent study by Strong et al reported that this had "the greatest contour accuracy" when compared with freehand bending in cadaveric orbits. 7 However, they also noted that stereolithographic modeling incurred the highest cost. 7 Currently, the price of anatomical models outsourced to medical modeling companies can be considerable.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, they also noted that stereolithographic modeling incurred the highest cost. 7 Currently, the price of anatomical models outsourced to medical modeling companies can be considerable. Rapid prototyping models in the above cases were produced for less than $5 NZD each.…”
Section: Discussionmentioning
confidence: 99%
“…A cadaver-based study found no significant differences in volume restoration between patient-specific implants (PSI) moulded on a pre-injury stereolithographic model, self-bent titanium meshes, and preformed titanium meshes. 65 Preformed implants may be more advantageous because of versatility and costs. 65 Andrades et al 63 concluded that pre-bent titanium implants are superior in terms of optimal reconstruction in comparison to other implants.…”
Section: Contouringmentioning
confidence: 99%
“…65 Preformed implants may be more advantageous because of versatility and costs. 65 Andrades et al 63 concluded that pre-bent titanium implants are superior in terms of optimal reconstruction in comparison to other implants. In large defects (Jaquiéry III-VI), the implant contour becomes an increasingly important factor for repositioning the globe into a correct position.…”
Section: Contouringmentioning
confidence: 99%
“…The medical software's are capable of obtaining the 3D Computer Aided Design (CAD) model from the DICOM data [10,11]. For the current case study, Materialize MIMICS 18.0 software is used to generate a patient specific medical model.…”
Section: Ct Data To 3d Cad Modelmentioning
confidence: 99%